Reciprocidade entre indivíduo e organização e seus impactos sobre a satisfação e o comprometimento - Leite, Andrea Duarte de Souza Correa (2003)
Individual-organization reciprocity and affectivity are two phenomena present in organizational life and which have become research topics in the field of studies of organizational behavior. This study aimed to reinforce the empirical evidence about the relationships between individual-organization exchange cognitions and affectivity in the work context. For this purpose, five hypotheses inspired by an unprecedented study developed by Siqueira (2002b) were submitted to the empirical test. We counted on the use of a questionnaire composed of five validated scales, referring to the study variables, which assessed perception of organizational support (PSO), perception of organizational reciprocity (PRO), normative organizational commitment (CON), job satisfaction ( STR) and affective organizational commitment (COA). 275 professionals participated, 183 belonging to the administrative sector and 92 to the administrative-academic sector of a Higher Education Institution, located in the Greater ABCD Paulista region and located in the state of São Paulo. The study participants had an average age of 32 years, the majority (58.2%) being female, with higher education (39.6%) and average working time in the organization for four years. The collected data were organized in an electronic database for statistical treatment, when the SPSS (Statistical Package for the Social Scienses) application was used. Descriptive analyzes of the variables and analyzes of correlation and multiple regression were performed for the tests of the five hypotheses. All hypotheses have been confirmed. It is concluded, then, that the present study reinforces the propositions of Siqueira (2002b) about the pertinence of considering the three analyzed concepts (PSO, PRO AND CON) as part of the mental reciprocity scheme. Still, the results of the study reaffirm the evidence about the predictive capacity of the EMR on job satisfaction and affective organizational commitment. Finally, the data analysis points to the perception of organizational support as being the cognitive component of EMR with the greatest power of influence on job satisfaction and affective organizational commitment. Therefore, cognitions about social exchange relationships with organizations precede satisfaction and affective commitment, which, in turn, are important factors in favor of the organization, contributing to its effectiveness (AU)